Practice of Wagon Management Based on Shenhua Green Logistics Chain - Yan, Ying (Journal of Environmental Accounting and Management, 2026)
Freight cars as coal transport carriers play a crucial role throughout Shenhua green logistics chain. With the rational distribution of transport capacity, the efficient organization of transport, the constant improvement of equipment, the optimization of maintenance and the digitization, the railway wagon management of Shenhua has become a key strategy to achieve clean energy development. The capacity of Shenhua railway freight volume has now reached 3.46 tons by rational distribution of wagon flow according to different vehicle types. The fixed marshalling and fixed train number on Shenhua railway is not only greatly reduces the operation of detaining, placing-in and taking-out cars as well as the wagon turnaround time. The operation procedures and time standards of cargo loading and unloading at the stations of Shenhua railway had been established. These standards have been optimized and improved in the wagon management work, and have improved the efficiency of vehicles use. After the Zhuan 8A bogie transformation, the train running speed of the empty car increased from 70km to 80km. Compared with C80, the capacity of KM98 could be increased by 20%, the efficiency of port loading and unloading could be increased 2 to 5 times, the energy consumption of unloading could be decreased more than 80%. By optimizing the distribution of railway freight car repair and maintenance equipment, the current annual Shenhua shop repair capacity has reached 6000 compared to the designed capacity of 5000 cars per year; and the current annual Shenhua depot repair capacity has reached 36800 compared to the designed capacity of repair of 34200 cars per year.